Petrology and geochemistry of Carboniferous volcanic rocks from the Awulale Iron Metallogenetic Belt in the West Tianshan Orogen (NW China): Constraints on petrogenesis and tectonic setting. (14th September 2018) - Wang, Bangyao; Jing, Delong; Zhang, Bo; Han, Ling; Jiang, Changyi
Abstract : The Awulale Iron Metallogenic Belt (AIMB) is the most largest submarine volcanic‐hosted iron metallogenic belts in Tianshan Orogen (NW‐China). The volcanic rocks from the Dahalajunshan Formation, extensively occurred in the western Tianshan Mountains, are mainly hosted‐iron rocks in the AIMB. In combination with published data, our new major and trace elements and isotopic data of volcanic rocks from the AIMB help define their petrogenesis and the tectonic evolution of the western Tianshan. The results indicate that these volcanic rocks belong to shoshonite, high‐K calc‐alkaline, and med‐K series with a small amount of tholeiite series, consisting mainly of basalt, trachybasalt, basaltic andesite, basaltic trachyte andesite, andesite, trachyte andesite, rhyolite, and dacite. They display similar geochemical features such as enrichment in large‐ion lithophile elements (LILE) and light REE (LREE), depletion in heavy REE and high‐field strength elements (HFSE), and prominent Nb‐Ta‐Ti negative anomalies, associated with the subduction‐related magmas. The basaltic and andesitic rocks show a more scattered range of initial 87 Sr/ 86 Sr ratios and higher positive εNd(t) values, whereas the acid volcanic rocks exhibit lower positive εNd(t) values with limited initial 87 Sr/ 86 Sr ratios. The basaltic rocks were derived from partial melting of phlogopite‐bearing mantle sources in the spinel stability field triggered by the slab‐released fluids of the subducted plate. The andesitic rocks originated by partial melting of mafic migmatites in response to metasomatism formed by early magmas derived from the mantle intruded into the crustal rocks. The acid volcanic rocks are likely derived from the partial melting of components in the lower crust. Therefore, the generation of the volcanic rocks in the AIMB is genetically linked to the geodynamic evolution of the western Tianshan from convergent subduction to collision during the Carboniferous. Both magmatism and hydrothermal processes control the mineralization, and in general, the parental magma of iron mineralization is basaltic and andesitic magma.